2000
DOI: 10.1046/j.1365-2362.2000.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine inhibition of the phosphorylation of cytoskeletal proteins from cerebral cortex of young rats is prevented by alanine

Abstract: In case the inhibition of cytoskeletal protein phosphorylation by phenylalanine also occurs in human phenylketonuria, it is possible that alanine supplementation to the phenylalanine-restricted diet may be beneficial to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We have previously demonstrated that the low stoichiometry of IF phosphorylation under basal conditions increases about 30% in rat brain slices exposed to toxic levels of metabolites , or toxins. ,, Conversely, hypophosphorylation has also been observed, reflecting misregulation of the phosphorylating system in response to different signals. In this context, different concentrations of (PhTe) 2 , from 5 to 100 μM, induced hypophosphorylation of GFAP and NF subunits mediated by activation of protein phosphatase 1 (PP1) in cerebral cortex of 9 and 15 day-old animals . Also, intracellular Ca 2+ levels were identified to be upstream of the signaling pathways targeting the cytoskeleton.…”
Section: Introductionmentioning
confidence: 97%
“…We have previously demonstrated that the low stoichiometry of IF phosphorylation under basal conditions increases about 30% in rat brain slices exposed to toxic levels of metabolites , or toxins. ,, Conversely, hypophosphorylation has also been observed, reflecting misregulation of the phosphorylating system in response to different signals. In this context, different concentrations of (PhTe) 2 , from 5 to 100 μM, induced hypophosphorylation of GFAP and NF subunits mediated by activation of protein phosphatase 1 (PP1) in cerebral cortex of 9 and 15 day-old animals . Also, intracellular Ca 2+ levels were identified to be upstream of the signaling pathways targeting the cytoskeleton.…”
Section: Introductionmentioning
confidence: 97%